Wonkenstein - Skye, Obert (New York : Henry Holt, 2011)
Twelve-year-old Rob has stuffed his closet with old laboratory experiments, unread books, and more, and when a creature emerges from that chaos causing a great deal of trouble, Rob has to do such horrible things as visit a library and speak at a school assembly to set things right again.
The closet door -- Saturday chores -- An unexpected visitor -- The thing -- Driven to madness -- Searching -- Forcing things -- Taffy -- Lock your doors -- Saved by candy -- Fizzy -- Nobody listens anymore -- From bad to worse -- Drama -- The closet -- Knock knock.
"Christy Ottaviano Books."
Accelerated Reader
Keywords: Monsters -- Juvenile fiction; Conduct of life -- Juvenile fiction; Books and reading -- Juvenile fiction; Schools -- Juvenile fiction; Families -- Juvenile fiction; Monsters -- Fiction; Conduct of life -- Fiction; Books and reading -- Fiction; Schools -- Fiction; Family life -- Fiction; Humorous stories; Monstres -- Romans, nouvelles, etc. pour la jeunesse; Morale pratique -- Romans, nouvelles, etc. pour la jeunesse; Livres et lecture -- Romans, nouvelles, etc. pour la jeunesse; Écoles -- Romans, nouvelles, etc. pour la jeunesse; Familles -- Romans, nouvelles, etc. pour la jeunesse; Books and reading; Conduct of life; Families; Monsters; Schools; Monsters -- Fiction; Conduct of life -- Fiction; Books and reading -- Fiction; Family life -- Fiction; Humorous stories; Humorous stories; Humorous fiction; Humorous fiction; Fiction; Juvenile works; Humorous fiction; Humorous fiction